Mobile application for restaurant recommendation using Geofencing technique / Nur Maizurah Nor Afendi - Nor Afendi, Nur Maizurah (2020)
Since a lot of people are working in this century, eating outside has become an essential element as people don’t have enough time to prepare food or even going back home to eat during a certain time. Furthermore, a lot of people are also enjoying eating outside and many tourists also like to explore the culture and the food of the country while going to restaurants. But there are many problems faced while finding the perfect restaurant, as an example, most people especially people in a foreign area, find it hard to know where to go to eat. Furthermore, finding a restaurant is hard as a lot of aspects needed to be considered such as the cuisine provided, the restaurant environment, the budget and the location of the restaurant. Thus, the objective of this system is to design a recommendation system based on the customer’s current location and preferences such as their budgets, cuisine provided, and the environment of a restaurant that they desired and to test the functionality of the system. In this system, the geofencing technique is applied to find a nearby restaurant based on the customer’s location. The rule-based technique is also used to filter the restaurant based on customer’s preferences. Customer can find their desired restaurant and order food using this application. To complete this project, the waterfall model is used as the methodology. The functionality testing for the application shows that the application works appropriately and have achieved the project objective. For future recommendation, this application can add a few features to enhance customer’s experiences such as give customers the ability to book a table at a restaurant, GPS navigation from the customer’s location to the restaurant they desired, and delivery option for each restaurant.